If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + 11 = 5(x + 2) Reorder the terms: 11 + Y = 5(x + 2) Reorder the terms: 11 + Y = 5(2 + x) 11 + Y = (2 * 5 + x * 5) 11 + Y = (10 + 5x) Solving 11 + Y = 10 + 5x Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + Y = 10 + -11 + 5x Combine like terms: 11 + -11 = 0 0 + Y = 10 + -11 + 5x Y = 10 + -11 + 5x Combine like terms: 10 + -11 = -1 Y = -1 + 5x Simplifying Y = -1 + 5x
| x=0.001x^2+2.9x-1000 | | f(x)=x^2-8 | | (1/8)x=0 | | -5=3(w-6)+8 | | -5=3(w-6)-8 | | 6f-(-5-2f)=4 | | 13x+2=28 | | x=3-(1/8)x | | 5m-20=-29+8m | | 9s-6=-6+7s | | 5x^2+36=24x | | 28x^2= | | -4x-16= | | 8x-72= | | 8*2/16 | | 2x^2-20x+18= | | 5(4-m)+8=-9(7m-10)+2 | | 3w^2+15=99 | | x*x*x=11 | | (-6y+5)(-5y+2)=0 | | n^3+6n^2+8n=759 | | f(x)=7x^2+9 | | 2x-10.2= | | 4x-26.0= | | 7v-4=6v-(4-3v) | | n-6-9n=2n+27+3n | | 3x-3.6= | | 1000x+888-6555=14-100x | | 3x-10.8= | | 1000x+888-6555=14 | | 8k-4k=20 | | 41/42*36 |